2007
DOI: 10.1002/eji.200636600
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of NK cytotoxicity by the IAP family member Livin

Abstract: Natural killer (NK) cells are part of the innate immune system, capable of killing tumor and virally infected cells. NK cells induce apoptosis in the target cell by either granule-or receptor-mediated pathways. A set of inhibitory and activation ligands governs NK cell activation. As transformed cells often attempt to evade NK cell killing, up-regulation of a potential anti-apoptotic factor should provide a survival advantage. The inhibitor of apoptosis protein (IAP) family can inhibit apoptosis induced by a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…We previously showed that noncleavable Livin protects cells from human NK cell-induced cytotoxicity (6). Here, we show in vivo using NK-deficient mice (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We previously showed that noncleavable Livin protects cells from human NK cell-induced cytotoxicity (6). Here, we show in vivo using NK-deficient mice (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…We generated retroviral constructs by subcloning the Livin cDNA into the pWZL IRES-blasticidin (subcloned into EcoRI-BglII sites) and pBabe-neomycin (subcloned into EcoRI-Sal1 sites) vector systems. Livin mutants were described previously (4,6,7). We created amphotropic retroviruses by transient cotransfection of 10-cm plates of 293T cells with 3 Ag of appropriate packaging plasmid pCL-10A1 for Moloney-based virus infections and CMV R8.91, CMV-VSV-G for lentiviral infections (P lentilox 3.7), and 5 Ag of carrier vector using FuGene 6 (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…apoptosis of Jurkat cells (21). Therefore, it is perplexing to illustrate the diverse roles Livin isoforms play, but isoformspecific therapy might offer an alternative opportunity to target tumors in the near future.…”
Section: Livin Biologymentioning
confidence: 99%
“…We previously found that Livin is specifically cleaved by caspases at the Asp52 residue to produce a large C-terminal fragment, containing both the BIR and the RING domains. After cleavage, truncated Livin (tLivin) acts paradoxically as a proapoptotic factor (18,19).In the present study we show that chemoresistant melanoma primary cultures that highly express the Livin protein are sen-* Corresponding author. Mailing address:…”
mentioning
confidence: 92%
“…We previously found that Livin is specifically cleaved by caspases at the Asp52 residue to produce a large C-terminal fragment, containing both the BIR and the RING domains. After cleavage, truncated Livin (tLivin) acts paradoxically as a proapoptotic factor (18,19).…”
mentioning
confidence: 99%